Demand-Oriented Approach to Estimate the Operational Performance of Urban Networks With and Without Traffic Information Provision - Tsekeris, Theodore; Stathopoulos, Antony (European Journal of Transport and Infrastructure Research, 2005)
This paper addresses the problem of estimating the operational performance of extended urban transport networks under different conditions of traffic information availability. The suggested approach employs a simulation procedure for the real-time estimation of the network state, based on the dynamic assignment of an O-D matrix, which is adjusted by the prevailing traffic conditions. Next, a different procedure is used for the online simulation of the route diversion behavior of users under the influence of route guidance information. Moreover, the approach provides the prediction of the network state by hypothesizing about the adjustment of the travel behavior of users to the new traffic conditions generated by the routing information. The implementation of the approach on a part of a real urban network led to the determination of suitable information updating frequencies for providing the largest improvements in the various performance measures. The results signify the important role of taking into account dynamic changes in the O-D demand size for the plausible evaluation of the impact of information provision on the network performance for real-time traffic operations and transport planning purposes.